Modelling of a new form of nitrogen doped activated carbon for adsorption of various dyes and hexavalent chromium ions - Mohamed A. El-Nemr; Uyiosa Osagie Aigbe; Kingsley Eghonghon Ukhurebor; Kingsley Obodo; Adetunji Ajibola Awe; Mohamed A. Hassaan; Safaa Ragab; Ahmed El Nemr (Scientific Reports)
Abstract This study reports a new form of nitrogen-doped activated carbon (AC5-600) produced from a blend of sawdust (SD) and fish waste (FW) treated with urea and ZnCl2 for the adsorption of toxic metals and dyes. The adsorbent was also explored in the treatment of acid brown 14 (AB14) and acid orange 7 (AO7) dye molecules and hexavalent chromium (Cr6+) ions. The pH controls the sorption of individual contaminants, with an observed superlative % of individual contaminants removed at pH 1.5. Removal at pH was credited to the electrostatic interaction (EI) between the anion dyes and Cr6+ species at this pH and the protonated sites accessible on the AC5-600 adsorbent surface. Based on the error values obtained from the non-linear modelling (NLM) of the kinetic and isotherm models, the Elovich (ELM-AB14 and Cr6+), pseudo-first- (PFOM-AB14) and second-order models (PSOM-AB14, AO7 and Cr6+) and the Freundlich (FRHM) model were found to ideally define the sorption of the various contaminants. The determined maximum sorption capacity (Q m) based on the NLM was 1114, 1929 and 318 mg.g-1 for AB14 dye, AO7 dye and Cr6+ ions, respectively. Based on the computational adsorption calculations, the sorption energies for the AO7 and AB14 dyes were -4.492 and -8.090 eV and 2.563, 1.789, 1.226 and 1.928 eV for Cr2, CrO3, CrO4, and CrO4H species. AB14 and AO7 dyes and Cr6+ ions adsorption to synthesised AC5-600 was predicted employing the response surface methodology (RSM) and artificial neural network (ANN) models. The ANN model was more effective in predicting AB14 and AO7 dyes and Cr6+ ions adsorption than the RSM, and it was highly applicable in the sorption process.